Anais Da IV Escola Regional De Engenharia De Software (ERES 2020) 2020
DOI: 10.5753/eres.2020.13736
|View full text |Cite
|
Sign up to set email alerts
|

Towards a Process for Migrating Legacy Systems into Microservice Architectural Style

Abstract: Microservice architectural style is a paradigm to develop systems as a suite of small and autonomous services, communicating thought a lightweight protocol. Currently, the most common way of adopting microservice architectures is by the modernization of legacy monolith systems. The migration of a legacy system into a microservice architecture is not a trivial task. In addition, there is a lack of recommendation or guidelines on how to perform such process. In view of this, this paper presents a preliminary pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 17 publications
0
5
0
Order By: Relevance
“…Wolfart et al approach the migration topic more holistically in their workin-progress paper [17]. They analyzed six primary studies to come up with a unified process.…”
Section: ) Migration Processmentioning
confidence: 99%
See 2 more Smart Citations
“…Wolfart et al approach the migration topic more holistically in their workin-progress paper [17]. They analyzed six primary studies to come up with a unified process.…”
Section: ) Migration Processmentioning
confidence: 99%
“…Figure 2 shows our proposed architecture-centric framework for migrating to microservices. It incorporates ideas and groundwork of existing research, especially the works by Wolfart et al [17,16]. Aspects of the works by Taibi et al [14] and Bozan et al [5] have influenced the design as well.…”
Section: ) Migration Processmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous scholars have established several models and methods to help in the implementation of legacy systems modernisation [27][28][29]. However, the aspects involved were studied separately and were not comprehensive.…”
Section: Introductionmentioning
confidence: 99%
“…However, the aspects involved were studied separately and were not comprehensive. Most of the studies suggested strategies and methods as well as implementation processes from a technical perspective [29,30]. They were also not specialised in the public sector and do not emphasise the importance of a citizen-centric digital government transition.…”
Section: Introductionmentioning
confidence: 99%